Essential Visual Studio 2019 : Boosting Development Productivity with Containers, Git, and Azure Tools - Johnson, Bruce (Computing consultant) (Apress L.P., 2020)
Discover how Visual Studio 2019 can improve your development process. Visual Studio is an integral part of the daily life of millions of developers worldwide. Even as this rich integrated development environment approaches two decades, it has never ceased in innovating ways to make developers work life more productive. Essential Visual Studio 2019 offers explicit guidance for the developer who is already familiar with Visual Studio, but might feel a little lost when it comes to understanding the more recent features and advances of the IDE. Busy developers simply dont have the time to digest and distill what the latest and greatest tools are with each version. As a result, useful process and performance features may be overlooked. This book, by simply focusing on the most recent innovations in Visual Studio and its tangential developer market, is the perfect "go to" for bridging that gap. Be ready to plunge headfirst into key features and advances that have been added, expanded, or improved, and topics such as unit testing, refactoring, Git, debugging, containers, and more. You will procure the basic concepts and value first, before diving into hands-on code that is designed to quickly get you up and running. The goal of this book is to bring the developer up to speed on Visual Studio 2019. It does not focus just on functionality added in Visual Studio 2019, but on takes a deep dive into the areas where Visual Studio 2019 changed. That way, even if youre coming from much earlier versions of Visual Studio, you can easily discern how upgrading to Visual Studio 2019 can make you more productive. What You Will Learn Know how the new features and improvements in Visual Studio 2019 can make you more productive Understand the value of modifications and when they can be used to take full advantage of this powerful IDE Review changes to Visual Studio over the last two versions and see where the development process is heading Discover the cloud-based, containerized, dev-ops-aware, and platform-flexible aspects of Visual Studio Gain clarity on the areas that have the greatest impact to you personally This book is for developers who use Visual Studio on a daily basis. Familiarity with earlier versions is helpful, as the book is not a soup-to-nuts survey of the IDE and some basic functions will not be covered. Bruce Johnson is co-founder and partner at ObjectSharp Consulting. With more than three decades of experience, he has expertise in rich client application development, web applications and API, microservices, and front end development. Formerly a Microsoft Certified Trainer (MCT), Bruce enjoys teaching and presenting in the developer community. He is currently co-president of the Metro Toronto .NET User Group and is the author of many books, articles, and columns